Airports' Sustainability Strategy: Evaluation Framework Upon Environmental Awareness - Dimitriou, Dimitrios; Karagkouni, Aristi (Frontiers in Sustainability, 2022)
Global sustainability challenges are reshaping how businesses operate in the 21st century. The necessary condition of ensuring economic, social, and environmental sustainability, also affects the functioning of regulatory authorities and businesses, particularly in the air transport sector, which, by facilitating access to productive services and connectivity to markets, is a critical contributor to the economy. Businesses are increasingly being pressed by decision makers (e.g., stakeholders, shareholders, customers, employees, and society) to assess their socioeconomic impacts and manage their actions sustainably and resiliently. As a result, effective management is a top priority not only for airport operators and authorities, but also for the national and local economies in this competitive and economically sensitive environment. The purpose of this paper is to present an assessment tool for evaluating airport strategic plans and environmental reports, and address how corporate actions can promote sustainability in the frame of environmental awareness in operating large transport hubs. The assessment methodology is based on a comparative analysis between airports and regulatory authorities’ threshold. The role of sustainability in the air transport business ecosystem is depicted, demonstrating that its relationship to business performance is a significant barrier to business resilience and competition for planners, managers, and decision makers. The numerical application considers a group of 10 European International airports delivering international flights and business. Conventional wisdom is to provide the evaluation analysis framework for planning and managing capital-intensive transport hubs such as airports.